2019
DOI: 10.1371/journal.pone.0217218
|View full text |Cite
|
Sign up to set email alerts
|

Motivational determinants of physical education grades and the intention to practice sport in the future

Abstract: Self-Determination Theory (SDT) is amongst motivational frameworks the most popular and contemporary approach to human motivation, being applied in the last decades in several domains, including sport, exercise and physical education (PE). Additionally, Achievement Goal Theory (AGT) has presented evidence of how contextual factors may influence student's behavior in this particular context. The main purpose of this study was to analyze the motivational climate created by the teacher in the classroom, students'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
66
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(92 citation statements)
references
References 44 publications
11
66
0
7
Order By: Relevance
“…The study found evidence that teachers are important influencers on the environmental cues about BPN satisfaction, intrinsic motivation, dispositional factors (i.e., grit), and academic performance. The importance of the need-supportive environment to student motivation is well-documented in the literature [50,51] but the current study shows that more research is needed since the literature would benefit from examining in more detail grit as independent factors, if we are to create favorable climates that optimize student performance and wider academic benefits for young sport science college students. All in all, these findings have important implications for instructional practice and highlight the importance of increasing teaching skills to provide autonomy support to students, particularly for college students with low resilience and perseverance levels [47,52].…”
Section: Discussionmentioning
confidence: 81%
“…The study found evidence that teachers are important influencers on the environmental cues about BPN satisfaction, intrinsic motivation, dispositional factors (i.e., grit), and academic performance. The importance of the need-supportive environment to student motivation is well-documented in the literature [50,51] but the current study shows that more research is needed since the literature would benefit from examining in more detail grit as independent factors, if we are to create favorable climates that optimize student performance and wider academic benefits for young sport science college students. All in all, these findings have important implications for instructional practice and highlight the importance of increasing teaching skills to provide autonomy support to students, particularly for college students with low resilience and perseverance levels [47,52].…”
Section: Discussionmentioning
confidence: 81%
“…The relationship between teacher skills and student academic performance has been extensively studied (Taylor et al, 2014). Participative methodologies that focus the teaching-learning process on the student, positive corrections, and giving autonomy to students are associated with positive consequences (Gil-Arias et al, 2020), such as disciplined behaviors (Gutiérrez et al, 2010) and academic performance in PE (Cid et al, 2019). However, the very complex reality of PE lessons in secondary education sometimes forces the teacher to stop focusing on the students' academic performance to give priority to more controlled instructional approaches in order to avoid disruptive behaviors (Granero-Gallegos et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that by managing the learning environment in such a way that it meets the motivational demands of students, the PE teacher is able to positively influence the engagement in and attitude towards PA within PE [4][5][6][7][8]. However, satisfying the motivational needs of every student is a complex task given the substantial heterogeneity present in PE-classes.…”
Section: Introductionmentioning
confidence: 99%